Preserving history through accounting: valuation and disclosure of archaeological sites and artefacts in the Malaysian public sector - Kamaluddin, Amrizah; Rosli, Mohamad Hafiz; Abdul Rahim, Memiyanty (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
The lack of efficient policy on valuing heritage assets (HA) impedes reporting these valuable country resources in the public sector’s financial statements. Delay in the valuation process of the artefacts collected through the archaeological work hinders historical information to be disseminated to the public. Without proper valuation procedures, public accountants face difficulties in justifying the high preservation cost of HA. The study aims to understand how archaeological sites and artefacts are valued, and to gather views from relevant agency officers on the expected accounting disclosures for these HA. A qualitative approach was used, with face-to-face interviews conducted with officials from the National Heritage Department, Archaeology Global Centre, and Museum Department to better understand how HA are valued in Malaysia. The study’s findings offer guidance to the government on how to account for HA under accrual-based accounting. The study proposes disclosure indicators for HA to enhance transparency and accountability in public sector reporting. In line with the Sustainable Development Goals, these indicators aim to share valuable information about the country’s heritage for the benefit of the public and future generations.